Temporal analysis of microRNAs associated with wing development in the English grain aphid, Sitobion avenae (F.) (Homoptera: Aphidiae). (March 2022) - Li, Xiangrui; Zhang, Fangmei; Coates, Brad; Wei, Changping; Zhu, Xun; Zhang, Yunhui; Zhou, Xuguo
Abstract: Molecular mechanisms underlying wing evolution and development have been a point of scientific inquiry for decades. Phloem-feeding aphids are one of the most devastating global insect pests, where dispersal of winged morphs lead to annual movements, migrations, and range expansions. Aphids show a polyphenic wing dimorphism trait, and offer a model to study the role of environment in determining morphological plasticity of a single genotype. Despite recent progresses in the genetic understanding of wing polyphenism, the influence of environmental cues remains unclear. To investigate the involvement of miRNAs in wing development, we sequenced small RNA libraries of the English grain aphid, Sitobion avenae (F.) across six different developmental stages. As a result, we identified 113 conserved and 193 S. avenae -specific miRNAs. Gene Ontology and KEGG pathway analyses of putative target mRNAs for the six differentially expressed miRNAs are enriched for wing development processes. Dietary uptake of miR-263a, miR-316, and miR-184a agomirs and antagomirs led to significantly higher mortality (>70%) and a lower proportion of winged morphs (<5%) . On the other hand, wing malformation was observed in miR-2 and miR-306 agomirs and miR-2 and miR-14 antagomirs, respectively, suggesting their involvement in S. avenae wing morphogenesis. These combined results not only shed light on the regulatory role of miRNAs in wing dimorphism, but also provide potential novel targets for the long-term sustainable management of S. avenae, a devastating global grain pest. Graphical abstract: Image 1 Highlights: Phenotypic plasticity in wing development is associated with microRNAs (miRNAs). Temporal miRNA expression profiles across six developmental stages were sequenced. Differentially expressed miRNAs between winged and wingless morphs were identified. The miRNAs miR-2, -14, and -306 are involved in wing morphogenesis. miR-263a, -316, and -184a influence the survival and wing polyphenism.